Translating test items into Norwegian – without getting lost in translation? - Mosvold, Reidar; Fauskanger, Janne; Jakobsen, Arne; Melhus, Kjersti (NOMAD Nordic Studies in Mathematics Education, 2009)
In relation to the Learning Mathematics for Teaching (LMT) project, sets of measures were created in order to analyse teachers Mathematical Knowledge for Teaching (MKT). This article presents some of the challenges and complexities involved in an attempt to translate and adapt these measures for use with Norwegian teachers. The measures were originally created for use in a U.S. context only, and a number of differences between the two countries contribute to increase the difficulty of doing this. Our study builds upon a similar Irish study, and this article points to some similar and several additional issues that arise when attempting to translate and adapt the measures for use in Norway.